Upcycling Used Cement Sacks into Wayang Beber Paintings: A Participatory Approach to Environmental Sustainability and Cultural Preservation in Rural Schools - Gandung Senatama; Nasikhun Amin; Alvina Rizqy Octivani; Azril Azifambayunasti; Luthfi Alif Dinar Choirunnisa (Aktualisasi Pengabdian Masyarakat, 2026)
The increasing accumulation of industrial waste, particularly used cement sacks that are difficult to decompose naturally, has become a significant and pressing environmental problem. The traditional art of Wayang Beber, as a national cultural heritage, also faces a slow but real threat of degradation, due to the decreasing relevance of its conventional presentation medium among the younger generation. This study aims to explore the potential of used cement sacks as an alternative medium for Wayang Beber paintings, while also evaluating their contribution to the reduction of non-organic waste and the revitalization of traditional art. This study uses a Participatory Rural Appraisal (PRA) model, which was implemented in two locations: SDN Widoro and MI Guppi Widoro. The experimental results show that the physical characteristics of cement sacks, including their absorbency and distinctive surface texture, present a new aesthetic dimension that enriches the visual expression of Wayang Beber. Utilization of this material also significantly contributes to the reduction of industrial waste, in line with the principles of sustainable development. The positive response from the community, especially the younger generation, indicates that a recycling-based approach can increase the appeal of traditional art without sacrificing its cultural authenticity. For the sustainability value, this activity is carried out periodically with further development of batik motifs.